Interactions between Turkish and Egyptian Islamic thinkers from 1908 to 1952: Modernity and the disruption of Islamic knowledge - Hammond, A (2019)
This thesis is an intellectual history of Late Ottoman Muslim thinkers and how they managed the epistemic disruption of nationalism, Islamic modernism, and the emerging discourse of Salafism. It studies the poet Mehmed Akif (1873-1936), sheikh ül-Islam Mustafa Sabri (1869-1954), and his deputy Zahid Kevseri (1879-1952), all of whom chose exile in Egypt as radical secular forces seized power in republican Turkey. The thesis argues they were the most influential figures in Late Ottoman religious thought, with a lasting impact on Turkish and Arab Islamism that has been obscured by disciplinary conventions that define writers and historical fields along ethnic, linguistic, and national lines. Through a deep reading of Arabic and Ottoman texts it traces their engagement with the ideas of Muhammad ʿAbduh, Muhammad Iqbal, Nasir al-Din al-Albani, Sayyid Qutb, and Said Nursi, outlining a broad history of Islamic thought in the modern period.